Martyrdom of al-Hallaj and unity of the existence:the condemners and the commenders - Yusri Mohamad Ramli (Universiti Kebangsaan Malaysia, 2013)
Wahdat al-wujud is a very most polemical topic discussed in the world of Islamic Tasawwuf or Sufism since 2nd century of Islamic history. This issue continued to be debated from time to time until today. Wahdat al-wujud or Oneness of the Absolute Existent had made conflict between Muslim cholars. Some scholars become the supporters of this theory and some against this idea. One of the important figures related to this term was al-Hallaj. Al-Husayn ibn Mansur al-Hallaj was a controversial writer and teacher of Islamic mysticism. He is famous for his martyrdom for heresy at the hands of the Abbasid rulers which arousing admiration in some and repression on the others. The drama of his life and death has been considered a reference point in the history of Sufism.